PENGELOMPOKAN KABUPATEN/KOTA DI PROVINSI JAWA TENGAH BERDASARKAN JUMLAH PEREMPUAN (USIA 18+) KORBAN KEKERASAN DENGAN MENGGUNAKAN K-MEANS CLUSTERING - Evi Yulianti; Agus Sugandha (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
Violence against women is one of the cases that often gets attention and news in various mass media and electronic media today. In Komnas Perempuan's Annual Records, there were 406,178 cases of violence against women reported and handled throughout 2018. This number increased compared to the previous year's 348,466 cases. This study was conducted to try to group 35 districts/cities in Central Java into 3 clusters based on the number of women (age 18+) victims of violence. Grouping is done using the k-means cluster method. The regencies/cities in Central Java are grouped into 3 clusters, namely: cluster 1 there is 1 Regency/City with a high number of women (age 18+) victims of violence, cluster 2 there are 4 Regency/City with a high number of victims of violence. female (age 18+) victims of violence. moderate, and cluster 3 there are 30 districts/cities with a low number of women (age 18+) victims of violence.